Molecular Mechanisms of Clonorchis sinensis-Host Interactions and Implications for Vaccine Development - Koda, Stephane; Zhu, Xing-Quan; Zheng, Kui-Yang; Yan, Chao (Frontiers in Cell and Developmental Biology, 2022)
Infections caused by Clonorchis sinensis remain a significant public health challenge for both humans and animals, causing pyogenic cholangitis, cholelithiasis, cholecystitis, biliary fibrosis, and even cholangiocarcinoma. However, the strategies used by the parasite and the immunological mechanisms used by the host have not yet been fully understood. With the advances in technologies and the accumulated knowledge of host-parasite interactions, many vaccine candidates against liver flukes have been investigated using different strategies. In this review, we explore and analyze in-depth the immunological mechanisms involved in the pathogenicity of C. sinensis. We highlight the different mechanisms by which the parasite interacts with its host to induce immune responses. All together, these data will allow us to have a better understanding of molecular mechansism of host-parasite interactions, which may shed lights on the development of an effective vaccine against C. sinensis.